Ferroelectric Materials: Domain Wall Displacement is the Origin of Superior Permittivity and Piezoelectricity in BaTiO3 at Intermediate Grain Sizes (Adv. Funct. Mater. 7/2014). (February 2014) - Ghosh, Dipankar; Sakata, Akito; Carter, Jared; Thomas, Pam A.; Han, Hyuksu; Nino, Juan C.; Jones, Jacob L.
<x xml:space="preserve">Abstract</x> Domain walls in ferroelectrics are moved by the application of electric fields by J. L. Jones and co‐workers. The extent of this domain wall motion can be measured using high‐energy X‐ray diffraction. During the application of electric fields, Debye‐Scherrer cones diffract from the sample in transmission geometry. On page 885, the corresponding diffraction rings are measured on an area detector, and the contribution of domain walls to properties and functional behavior can thereby be analyzed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>